Citogenética de espécies de anfíbios (Anura) das Bacias Hidrográficas Taquari-Antas e Apauê Inhandava, RS e atividade antimicrobiana da secreção da pele de Rhinella henseli (Anura, Bufonidae) - Ficanha, Natália Cristine (2018)
The great morphological uniformity of the anurans makes them the most easily diagnosable among it may represent a new therapeutic perspective. The objective of this proposal is to: (1) characterize the cygenogenetic species in the two basins, comparing the results with each other and with those of other sites of occurrence, verifying the correct identification of the species and (2), to evaluate the antimicrobial activity of Rhinella henseli skin secretions, testing its action on the bacteria Staphylococcus aureus, Escherichia coli and the fungus Candida albicans. In this study, the species: Aplastodiscus perviridis, Leptodactylus latrans, Leptodactylus mystacinus, Physalaemus cuvieri, Physalaemus aff. gracilis, Boana faber, Leptodactylus plaumanni, Odontophrynus americanus, Melanophryniscus devincenzii, Rhinella henseli and Rhinella icterica were cytogenetically characterized by conventional staining (Giemsa) and differential chromosomes (Bandamento C and AgNOR). For the analysis of the antimicrobial activity, the secretion of R. henseli was obtained by subcutaneous injection of epinephrine, tested by the technique of bioautography. Our results verified that the species that were cytogenetically compared to each other and to those of other sites of occurrence, through studies already performed by other authors, did not present significant differences in the species-specific chromosome characteristics of the populations, and no evidence of cytogenetic alteration, thus concluding that the river basins did not represent, so far, geographical barriers capable of isolating populations. Through the antimicrobial study, we observed that in R. henseli the secretion extracted from its skin shows antimicrobial activity against yeast C. albicans, being this the first study of the antimicrobial action in this bufo.